Who Decides: Me or We? Family Involvement in Medical Decision Making in Eastern and Western Countries - Alden, Dana L.; Friend, John; Lee, Ping Yein; Lee, Yew Kong; Trevena, Lyndal; Ng, Chirk Jenn; Kiatpongsan, Sorapop; Abdullah, Khatijah Lim; Tanaka, Miho; Limpongsanurak, Supanida (SAGE Publications, 2018)
Background. Research suggests that desired family involvement (FI) in medical decision making may depend on cultural values. Unfortunately, the field lacks cross-cultural studies that test this assumption. As a result, providers may be guided by incomplete information or cultural biases rather than patient preferences. Methods. Researchers developed 6 culturally relevant disease scenarios varying from low to high medical seriousness. Quota samples of approximately 290 middle-aged urban residents in Australia, China, Malaysia, India, South Korea, Thailand, and the USA completed an online survey that examined desired levels of FI and identified individual difference predictors in each country. All reliability coefficients were acceptable. Regression models met standard assumptions. Results. The strongest finding across all 7 countries was that those who desired higher self-involvement (SI) in medical decision making also wanted lower FI. On the other hand, respondents who valued relational-interdependence tended to want their families involved – a key finding in 5 of 7 countries. In addition, in 4 of 7 countries, respondents who valued social hierarchy desired higher FI. Other antecedents were less consistent. Conclusion. These results suggest that it is important for health providers to avoid East–West cultural stereotypes. There are meaningful numbers of patients in all 7 countries who want to be individually involved and those individuals tend to prefer lower FI. On the other hand, more interdependent patients are likely to want families involved in many of the countries studied. Thus, individual differences within culture appear to be important in predicting whether a patient desires FI. For this reason, avoiding culture-based assumptions about desired FI during medical decision making is central to providing more effective patient centered care.